Improving Visual Information Access for Blind Students Using Crowdsourced Assistance Technology - Dwi Citolaksono; Fajar Indra Septiana (Al-Qalam Institue, 2026)
This study aims to explore how the Be My Eyes application supports independent visual information access among totally blind students, with particular attention to user preferences between volunteer-based assistance and AI-driven features. A qualitative exploratory design was employed involving five totally blind students, with data collected through semi-structured in-depth interviews and analyzed using thematic analysis. The findings reveal that participants strongly prefer the Be My AI feature over live volunteer assistance due to its perceived advantages in privacy, convenience, speed, and emotional comfort. The study also identifies that the main operational difficulty is not related to software accessibility but to users’ physical ability to align and frame the camera when capturing visual objects. Despite these challenges, Be My Eyes significantly enhances students’ autonomy by enabling independent access to visual information in daily activities, although human assistance remains necessary for complex or high-stakes tasks. The implications suggest that AI-based assistive technologies have strong potential to transform inclusive education by promoting flexible, user-centered, and self-reliant access to visual information for blind learners in special education contexts.